Polarization of Human Monocyte-Derived Cells With Vitamin D Promotes Control of Mycobacterium tuberculosis Infection - Rao Muvva, Jagadeeswara; Parasa, Venkata Ramanarao; Lerm, Maria; Svensson, Mattias; Brighenti, Susanna (Frontiers in Immunology, 2020)
Background: Understanding macrophage behavior is key to decipher Mycobacterium tuberculosis (Mtb) pathogenesis. We studied the phenotype and ability of human macrophages polarized with active vitamin D (1,25(OH)2D3) to control intracellular Mtb infection compared with polarization of conventional macrophage subsets, classical M1 or alternative M2. Methods: Human blood-derived monocytes were treated with active vitamin D or different cytokines to obtain 1,25(OH)2D3-polarized as well as M1- and M2-like macrophages or fully polarized M1 and M2 subsets. We used an in vitro macrophage Mtb infection model to assess both phenotype and functional markers ie. inhibitory and scavenger receptors, costimulatory molecules, cytokines, chemokines, and effector molecules using flow cytometry and quantitative mRNA analysis. Intracellular uptake of bacilli and Mtb growth was monitored using flow cytometry and colony forming units. Results: Uninfected M1 subsets typically expressed higher levels of CCR7, TLR2 and CD86, while M2 subsets expressed higher CD163, CD200R and CD206. Most of the investigated markers were up-regulated in all subsets after Mtb infection, generating a mixed M1/M2 phenotype, while the expression of CD206, HLADR and CD80 was specifically up-regulated (P < 0.05) on 1,25(OH)2D3-polarized macrophages. Consistent with the pro-inflammatory features of M1 cells, Mtb uptake and intracellular Mtb growth was signifcantly (P < 0.01-0.001 and P < 0.05-0.01) lower in the M1 (19.3%) compared with the M2 (82.7%) subsets 4 hours post-infection. However, infectivity rapidly and gradually increased in M1 cells at 24-72 hours. 1,25(OH)2D3-polarized macrophages was the most potent subset to inhibit Mtb growth at both 4 h and 72 h (P < 0.05-0.01) post-Mtb infection. This ability was associated with high mRNA levels of pro-inflammatory cytokines and the antimicrobial peptide LL-37 but also anti-inflammatory IL-10, while expression of the immunosuppressive enzyme IDO (indoleamine 2,3-dioxygenase) remained low in Mtb-infected 1,25(OH)2D3-polarized macrophages compared with the other subsets. Conclusions: Mtb infection promoted a mixed M1/M2 macrophage activation and 1,25(OH)2D3-polarized macrophages, expressing LL-37 but not IDO, were most effective to control intracellular Mtb growth. Macrophage polarization in the presence of vitamin D may provide the capacity to mount an antimicrobial response against Mtb and simultaneously prevent expression of inhibitory molecules that could accelerate local immunosuppression.